PENGARUH JENIS PELARUT EKSTRAKSI TERHADAP KADAR ALKALOID DALAM EKSTRAK TERIPANG (Paracaudina australis) MENGGUNAKAN SPEKTROFOTOMETRI UV-VIS - Aulya Sagita Rahma Sujana; Prisma Trida Hardani; Amanda Safithri Sinulingga (Klinikal Sains : Jurnal Analis Kesehatan, 2024)
Sea cucumbers are a type of marine organism that move slowly and live in shallow waters such as sand, mud, algae, coral reefs where sea cucumbers are a source of animal protein consumed by the public. Research on various types of sea cucumbers has shown that there are several bioactive compounds, one of which is alkaloids. Alkaloids are one of the secondary metabolite compounds that are often found in nature, such as in plant and animal tissues. Previous research results show that there are alkaloids in sea cucumber extract. The aim of this research is to determine how this limited type of solvent impacts the amount of bioactive compounds contained in sea cucumbers (Paracaudina australis). Qualitative and quantitative tests were carried out to test alkaloid compounds. Qualitative tests use color reactions with Dragendroff, Wagner and Mayer reagents. Quantitative tests were carried out using Uv-Vis spectrophotometry with a maximum wavelength of 273 nm. The standard solution used is caffeine. Quantitative analysis showed that all extracts with various solvents were positive for containing alkaloids. The highest alkaloid content is ethyl acetate extract with levels of 71.0116 ± 0.2872 ppm, then followed by acetone extract which is semipolar with levels of 22.6531 ± 0.2277 ppm and the lowest is chloroform extract with levels of 13.9622 ± 0.0283 ppm. Keywords: Sea cucumber; Alkaloids; Solvent Type; Uv-Vis Spectophotometry